Dance Intervention Impact on Brain Plasticity: A Randomized 6-Month fMRI Study in Non-expert Older Adults - Balazova, Zuzana; Marecek, Radek; Novakova, L’ubomíra; Nemcova-Elfmarkova, Nela; Kropacova, Sylvie; Brabenec, Luboš; Grmela, Roman; Vaculíková, Pavlína; Svobodova, Lenka; Rektorova, Irena (Frontiers in Aging Neuroscience, 2021)
Background: Dance is a complex activity combining physical exercise with cognitive, social and artistic stimulations. Objectives: We aimed at assessing effects of dance intervention (DI) on intra and inter-network resting-state functional connectivity (rs-FC) and its association to cognitive changes in a group of non-demented elderly. Methods: Participants were randomly assigned into two groups: DI and life as usual (LAU). Six-months-long DI consisted of supervised 60 min lessons three times per week. Resting state fMRI data were processed using independent component analysis to evaluate intra and inter-network connectivity of large-scale brain networks. Interaction between group (DI, LAU) and visit (baseline, follow-up) was assessed using ANOVA, and DI-induced changes in rs-FC were correlated with cognitive outcomes. Results: Data were analysed in 68 participants (DI; n=36 and LAU; n=32). Significant behavioural effect of DI was found in attention domain, with Z scores increasing in the DI group and decreasing the LAU group (p = 0.017). The DI as compared to LAU led to significant rs-FC increase of the default mode network and of specific inter-network pairings, including insulo-opercular and right frontoparietal/frontoparietal control networks (p=0.019 and p=0.023), visual and language/DMN networks (p=0.012 and p=0.015), and cerebellar and visual/language networks (p=0.015 and p=0.003). The insulo-opercular and right fronto-patietal networks crosstalk was associated with attention/executive domains Z-scores (R=0.401, p = 0.015, and R = 0.412, p = 0.012). Conclusion: The DI led to intervention-specific complex brain plasticity changes that were of cognitive relevance.